Employee share-ownership trusts and corporate governance. - Michie, J; Oughton, C (MCB UP Ltd, 2001)
he March 2000 Budget in the UK introduced tax incentives to encourage employee shareholding. The theory is that if employees feel that they have a stake in the enterprise or organisation in which they work, they will be more motivated and committed, with positive outcomes in terms of productivity and organisational performance. This theory has received support from research currently being conducted within the School of Management and Organizational Psychology at Birkbeck, University of London, which has found significant positive links between “progressive” human resource practices that promote participation and involvement on the one hand, and corporate performance and organisational outcomes on the other. This is in line with other recent research in the UK and internationally. The question both for business and government is how to engender such participation and involvement and, specifically, whether this can be brought about through employee shareholding, when such individual shareholdings, taken separately, are insignificant in terms of the overall share capital of the corporation. By pooling the voting rights – although not necessarily the actual ownership – of their shares, an employee shareholder trust could represent a significant voice. However, some mechanism is needed to translate individual employee shareholding stakes into a collective voice that can deliver results, both in terms of representing the interests of employees and in convincing employees that their shareholding gives them a stake in the enterprise. Such a move could have important beneficial effects for corporate performance and hence economic growth. It could also have significant welfare effects in terms of enriching the experience of working life.